2014
DOI: 10.1103/physrevlett.113.256401
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Near-Room-Temperature Quantum Anomalous Hall Effect on Honeycomb Materials

Abstract: Recently, this long-sought quantum anomalous Hall effect was realized in the magnetic topological insulator. However, the requirement of an extremely low temperature (approximately 30 mK) hinders realistic applications. Based on ab-initio band structure calculations, we propose a quantum anomalous Hall platform with a large energy gap of 0.34 and 0.06 eV on honeycomb lattices comprised of Sn and Ge, respectively. The ferromagnetic order forms in one sublattice of the honeycomb structure by controlling the surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
238
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(246 citation statements)
references
References 54 publications
6
238
0
2
Order By: Relevance
“…5,16 Thus, stanene has a great potential for photo-related applications than graphene. 87 Moreover, achieving ultra-low 21 work function in graphene is very important for electronics and electron emission devices. [89][90][91] As stanene and doped stanene have lower work function than graphene, they can be promising for electronic device technologies.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16 Thus, stanene has a great potential for photo-related applications than graphene. 87 Moreover, achieving ultra-low 21 work function in graphene is very important for electronics and electron emission devices. [89][90][91] As stanene and doped stanene have lower work function than graphene, they can be promising for electronic device technologies.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…20 and quantum anomalous Hall (QAH) effect near room temperature. 21 On the other hand, doped QSHI materials show time-reversal-invariant topological superconductivity. 22 Thus, doped stanene could be a promising material for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Garrity and Vanderbilt demonstrated that the GaN/EuO interface is a candidate for achieving a QAH state at temperature of around 70 K and with band gaps of about 0.1 eV [22]. Wu et al proposed that half-passivated stanene and germanene become Chern insulators with energy gaps of 0.34 and 0.06 eV, respectively [23]. The proposed FM order in this system comes from the unpassivated sublattice that exhibits dangling p orbitals.…”
mentioning
confidence: 99%
“…In contrast to other lighter materials (including graphene, silicene and germanene), stanene is characterized by strong spin-orbit coupling (SOC). The decorated stanene supports large-gap QSH state [5] as well as many other novel features, like enhanced thermoelectric performance [21], near room temperature quantum anomalous Hall (QAH) effect [22] and novel topological superconductivity [23]. These novel properties make stanene systems promising for fundamental research and future technologies.…”
mentioning
confidence: 99%